Self-Regulation in Early Childhood as a Relational Process in Early Childhood Education - Maisyaroh, Nurachmi (Qualitative Research in Early Childhood Education, 2026)
This study aims to understand early childhood self-regulation as a developmental process rooted in relationships, rather than merely as the result of discipline and behavioral control. Self-regulation in early childhood is often simplified as compliance with rules, thereby neglecting the emotional and relational aspects that form its developmental foundation. This study employed a qualitative approach using structured observation techniques involving young children in an early childhood education institution. Participants were selected through purposive sampling, considering variations in children’s self-regulation abilities. Data collection focused on emotional regulation behaviors, behavioral regulation, and forms of interaction between teachers and children during learning activities. Data were analyzed using thematic analysis to identify patterns of self-regulation emerging within relational contexts. The findings indicate that children’s self-regulation develops through co-regulation processes involving consistent and responsive emotional support from teachers. Children are not yet able to manage their emotions and behaviors independently without relational support from adults. Disciplinary approaches that emphasize compliance do not necessarily lead to healthy and sustainable self-regulation. This study emphasizes that secure relationships constitute the primary foundation for the development of self-regulation in early childhood. The findings contribute theoretically and practically to the development of early childhood education approaches that are more relationship-oriented and focused on children’s emotional well-being.